Influencia del desayuno en la nutrición y rendimiento académico de los estudiantes de tercero y cuarto año de básica de la Escuela Fiscal Miguel De Cervantes Los Ríos, periodo mayo-septiembre 2019. - Guin Delgado, Gladys Suleyka (2019)
Breakfast represents the main meal of the day, it has an important role in the child's physical and neurocognitive development, however there is bad attachment to it, causing problems in their nutritional status and academic performance. Objective: To establish the influence of breakfast on the nutrition and academic performance of the students in the third and fourth year of basic of the Miguel de Cervantes Baba fiscal school, the rivers. May-September 2019 period. Results: We worked with a total of 100 children from the Miguel de Cervantes Fiscal School, in the third and fourth grade of basic education, where 54% of them had breakfast as opposed to 46% who did not; Within the group of those who did have breakfast, 30% had a poor quality breakfast; the nutritional status isolated in 39% was obesity, of which 33% had poor school performance. Regarding the factors inherent to the parents, we have that 45% of the mothers indicated that they have between 2 and 3 children including the one who is as a student in the educational institution in which the study is carried out; 46% of the parents had a level of primary education; Finally, 86% of them did not have any knowledge about what a healthy breakfast or its components is.